How morphology influences relaxivity – comparative study of superparamagnetic iron oxide–polymer hybrid nanostructures. (7th July 2015) - Ebert, Sandro; Bannwarth, Markus B.; Musyanovych, Anna; Landfester, Katharina; Münnemann, Kerstin
Abstract : Superparamagnetic iron oxides (SPIOs) are widely used in MRI as T 2 contrast agents, and interest is still growing. Here, the T2 relaxivity of three different SPIO–polymer hybrid morphologies, i.e. homogeneously distributed iron oxide within a polymer matrix, Janus‐like nanoparticles and polymer nanocapsules containing iron oxides, is studied. Making use of calculations based on theory for agglomerated systems, the obtained T 2 values could be predicted for all different morphologies, except for nanocapsules. Nanocapsules, in contrast to full spheres, allow for water exchange between encapsulated water and bulk water, and thus have two contributions to relaxivity. One originates from the capsules acting as a weakly magnetized cluster and the other stems from the individual SPIOs inside the capsule. Therefore, the relaxivities were also computed using an empirical equation found in the literature, which considers water exchange, resulting in a better T 2 forecast for the nanocapsules. The presented study is the first example of a comparison between measured and calculated relaxivities of nanocapsules. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : Relaxivity of nanoparticles and nanocapsules loaded with superparamagnetic iron oxide is calculated and compared to experimental results. In case of semipermeable nanocapsules, the consideration of water exchange leads to an improved matching between experimental and calculated results.